Coverage of Pakistan in the New York Times during Donald Trump's first year in office. Issue 3 (2nd October 2019) - Moretti, Anthony
Abstract : Previous academic research has shown American news media agencies consider South Asia to be an unsafe and unhealthy region of the world. Research also has demonstrated when American geopolitical interests are at stake that U.S. media will support the president provided his policies are viewed as successful. Donald Trump entered the White House determined to stamp out terrorism, and he was especially critical of Pakistan as an ally in combating it. This research demonstrates that the New York Times focused on negative or bad news from Pakistan during 2017, which marked Trump's first year in office, despite the president making few public statements about the country in that year.